Polymorphism of p53 Codon 72 Gene on Cervical Cancer Incidence in Malay Population - Lusia Hayati; Siska Delvia (Archives of The Medicine and Case Reports, 2020)
In Indonesia, the cases of cervical cancer are estimated at around 50 per 100.000 people. Itwas estimatedthattherearemore than 1 millionwomenworldwidewho have cervical cancer,and most of them have not been diagnosed yet or do not have access to screening and medicaltreatment. P53 codon 72 polymorphism can affect the risk of cervical cancer through theregulation of proliferationandcellapoptosis.The purpose of this research was to investigate theassociation between p53 codon 72 polymorphism and cases of cervical cancer. This researchwas observational analytic research. The research was done by examining in the laboratory ofMolecular Biology, Faculty of Medicine, Universitas Sriwijaya by using a case-control studyapproach.Thesampleoftheresearchconsistedof 70 subjects,and they were divided into twogroups:35 in case group and 35 in the control group. The determination of genotype andallotype was done by using PCR-RFLP technics. The results of the research showed there wasa significant difference between p53 codon 72 polymorphism between the case group andcontrol group. The results of genotypes of p53 codon 72 polymorphism in the case groupwere seven respondents (20.0%) with Pro/Pro genotype, five respondents (14.3%) withArg/Arg genotype, and 23 respondents (65.7%) with Pro/Arg. While in control group, there were28 respondents (80.0%) with Pro/Pro genotype, 0 respondent (0.0%) with Arg/Arg genotype,and 7 respondents (20%) with Pro/Arg. The frequency of the Prolin allele in case group was 37(52.9%), and the Arginin allele was 33 (47.1%), while the frequency of the Prolin allele in thecontrol group was 63 (90%), and the Arginin allele was 7 (10%). The Chi-Squareofgenotypewasvalued0.000,OR1,304andCI95%1,071-5,891,whiletheallelewas valued 0.000, OR 8.027 andCI 95% 3.228-19.962. There was anassociation between genotype and allele of p53 codon 72polymorphismandcases of cervicalcancer.